PENERAPAN SANKSI PIDANA MATI DALAM TINDAK PIDANA KORUPSI TERHADAP DANA BANTUAN SOSIAL (BANSOS) KONDISI DARURAT DIHUBUNGKAN DENGAN PENGAMBIL KEPUTUSAN - Abu Bakar Siddiq; Deny Haspada (Scientia Regendi, 2022)
Elucidation of Article 2 paragraph (2) of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption is formulated that: a state of danger in accordance with applicable laws and regulations, in the event of a national natural disaster occurring , as a repetition of criminal acts of corruption, or when the country is in a state of economic and monetary crisis.” The research method used is a normative juridical approach and a normative juridical research specification. While the data analysis used a qualitative juridical method. The basis for the weighting reason for corruption, as done by Julian Peter Batubara. The basis for using covid 19 as a ballast reason is Presidential Decree No. 11 of 2020 concerning the Determination of Public Health Emergency Corona Virus Disease 2019 (Covid 19) and Presidential Decree No. 12 of 2020 concerning the Determination of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 (Covid 19) and in a state of emergency. The perpetrators of criminal acts of corruption can be sentenced to the death penalty. If the suspicion is then that the indictment is only related to Article 11 or Article 12, it cannot be prosecuted and sentenced to death, it can be sentenced to death if there is use of Article 2 of the Anti-Corruption Law in that case. Keywords: Death Penalty, Social Assistance Corruption, Decision Makers